Memahami Lebih Dalam tentang Teori Siklus Hidup, Model Kontinum Rekod dan Konsep Arsip Total untuk Implementasi di Institusi dan Organisasi - Putra, Purwanto; Purnamayanti, Arnila; Maryani, Eri (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2023)
This This article attempts to explore and compare the descriptive analysis of the development of the record management system paradigm over time. The aim is to examine the potential implications of applying the lifecycle theory approach to archives, the continuum record model, and the concept of vital records. Each of these approaches was developed in different periods and places, such as the archive lifecycle in the United States, the record continuum model in Australia, and the total archive concept in Canada. This article also investigates the differences and possible relationships among these three approaches as alternatives to complement the widely and traditionally used lifecycle theory approach in archiving activities in Indonesia. The study is conducted through a literature review using a qualitative and interpretative paradigm. Relying on historical and narrative analysis, the findings of this study provide evidence of the record management theories' practices within organizations. The study concludes that the record management practices in organizations can be improved by giving adequate attention to specific factors in each record management approach during implementation. Currently, the lifecycle theory remains dominant, but it is unable to address various challenges and issues in archiving. The continuum record model offers a more specific way to organize and support the preservation of electronic and digital archives, which are increasingly held by modern institutions or organizations not entirely covered by the lifecycle theory approach. Similarly, the total archive concept can be used as a strategy for documenting records and archives that possess historical context and institutional memory. However, there are still gaps in each approach that require further analysis of their key components to bridge these gaps and enable their holistic implementation in various archival institutions and organizations in Indonesia in the future.